Treatment options for COVID-19 (disease caused by coronavirus) by means of physiotherapy, under special consideration of the results gained in phototherapy (Academic Journal of Internal Affairs, 2021)
The coronavirus affects the whole humanity and the epidemic influences all aspects of our lives. So far, the current treatment options are very modest. The risk of COVID-19 is significantly increased in hospitals and various social institutions. The exposure of law enforcement and health care workers to higher viral concentrations is significant in the treatment of particularly severe patients. Currently, all healthcare workers are on the front lines. Everyone works a lot, is exhausted and is under constant stress. In the last few months, several articles have appeared in the international literature that the possibility of soft laser therapy should be used in treatment as well as prophylactically. The spread of the disease and the epidemic can be prevented by early detection, isolation, vaccine, and rapid therapeutic care of patients.
Keywords: COVID-19; ARDS; cytokine storm; soft laser therapy